Sorption of Cr(VI) and Cu(II) in aqueous solution by ethylenediamine modified rce hull - Tang, P.L.; Lee, C.K.; Low, K.S.; Zainal, Z. (Selper, 2003)
The sorption characteristics of Cr(VI) and Cu(II) by ethylenediamine modified rice hull from single and binary metal ion solutions were evaluated under various experimental conditions. Optimal Cr(VI) and Cu(II) removal from single metal ion solutions occurred at pH 2.0 and 5.5, respectively. Simultaneous removal of Cr(VI) and Cu(II) occurred at pH greater than 3.0. The sorption kinetics of Cr(VI) and Cu(II) from single and binary metal ion solutions were studied with reference to metal concentration, agitation rate and particle size. Sorption of Cr(VI) was more rapid than Cu(II). The kinetics of metal ion sorption fitted a pseudo-second order expression. The variation in the initial uptake rates was very small at an agitation rate beyond 150 rpm and sorption was generally independent of particle size. Equilibrium sorption data could be fitted into the Langmuir isotherm equation. Maximum sorption capacities of ethylenediamine modified rice hull for Cr(VI) at pH 2 and Cu(II) at pH 4 in single metal solutions were 0.45 and 0.06 mmol g−1, respectively. This corresponds to an enhancement factor of 2.6 and 3 fold for Cr(VI) and Cu(II), respectively, compared to natural rice hull. A synergistic effect was observed for sorption of these ions in binary metal solutions.